NEW PRINCIPLES OF CONSTRUCTION CRYPTOGRAPHIC PRIMITIVES OF NONLINEAR SUBSTITUTIONS - Белецкий, Анатолий Яковлевич; Навроцкий, Денис Александрович; Семенюк, Александр Иванович (Ukrainian Information Security Research Journal, 2015)
Classic primitives nonlinear substitution, as a representa-tive of which you can specify, for example, primitive Sub-byte algorithm Rijndael, is as simple as replacing each character encrypted text on a fixed symbol of the same alphabet, actually realizing the transformation one alpha-bet simple substitution cipher. A distinctive feature of these primitives is that they do not alter the frequency distribution of characters in the cipher text compared with the distribution of frequencies in clear text. And as a consequence of the marked features of primitives – cipher text entropy coincides with the entropy of the source text. The paper discusses the various options for randomiza-tion primitives nonlinear substitution, which resulted in a significant increase in entropy is achieved output text, with the cryptograms acquires properties similar to those of white noise.